The Ottoman Approach to Scientific Classification in Tafsir History: A Study of Taskopruluzade Ahmad Efendi’s ‘Miftâhu’s-Saâde’ - Hariani, Hidayah (UIN Sunan Kalijaga Yogyakarta, 2023)
This study presents an analytical investigation of the historical aspect of tafsir within the Ottoman tradition, as found in the literary composition